The ludic takes work - Koutsouras, Panagiotis; Martindale, Sarah; Crabtree, Andy (2017)
Games that revolve around user-generated content have been explored mainly from a ludic perspective, leaving the work practices that are entailed in content production underexplored. What we argue in this paper is that there is an underlying economy in Minecraft’s community, which plays a significant role in the game’s current form. Our ethnographic fieldwork revealed the various aspects of the work of producing in-game content, by teasing out the discrete segments of the arc of work of commissioning, creating and delivering a Minecraft map. The infrastructure this work relies on is fragmented though, with the various accountability systems in place being appropriations by the players themselves. This raises a number of design implications related to how members coordinate tasks and articulate their work.